1, 4‐Diiodobenzene with –COO–TEMPO (TEMPO = 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl‐4‐yl) substituents at 2, 5‐positions: synthesis and use as a monomer for new π‐conjugated polymers having nitroxyl radicals in side chains. (19th July 2013) - Iijima, Takayuki; Abe, Masahiro; Koizumi, Take‐Aki; Fukaya, Atsushi; Usami, Kyohei; Kami, Kenichiro; Yamamoto, Takakazu
<x xml:space="preserve">Abstract</x> The reaction of 2, 5‐diiodo‐1, 4‐benzenedicarbonyl chloride, C6H2I2(COCl)2‐p, with 4‐hydroxy‐2, 2, 6, 6‐tetramethyl‐1‐piperidinyloxy (TEMPO‐ol) gave I–Ph(COO–TEMPO)2–I, Monomer‐1. Pd‐catalyzed polycondensation of Monomer‐1 with Me3Sn‐Th‐SnMe3 (2, 5‐bis(trimethylstannyl)thiophene) and Bu3Sn–CH = CH–SnBu3 (1, 2‐bis‐(tributylstannyl)ethylene) gave the corresponding π‐conjugated polymers, Polymer‐1 and Polymer‐2, respectively. Monomer‐1 was converted to a diethynyl compound, H–C ≡ C–Ph(COO–TEMPO)2–C ≡ C–H (Monomer‐1'), and Pd‐catalyzed polycondensation between Monomer‐1 and Monomer‐1' gave a π‐conjugated poly(arylene ethynylene) type polymer, Polymer‐3. According to the expansion of the π‐conjugation system by the polymerization, the UV–vis peaks of Monomer‐1 (λmax = 323 nm) and Monomer‐1' (327 nm) are shifted to longer wavelengths (λmax = 365 nm, 385 nm, and 396 nm for Polymer‐1, Polymer‐2, and Polymer‐3, respectively). Polymer‐1–Polymer‐3 showed ESR signals at about g = 2.01 with reasonable intensities. They are electrochemically active and showed a peak current anodic (oxidation) peak at about 0.9 V versus Ag/AgCl, which is reasonable for TEMPO polymers. Copyright © 2013 John Wiley & Sons, Ltd.